Participation to avoid elite capture in communication policies: Lessons from Latin America - Segura, Maria Soledad (2023)
How did participatory state institutions of communication policies created in Argentina, Ecuador, Mexico, and Uruguay face capture by political and economic elites? In this article a comparative approach is used to answer this question. The research addresses regulation and its implementation based on the methodological guide provided by the concept of citizen participation. Diversity, implementation, incidence, autonomy, and transparency are the axes that organized the analysis, which includes qualitative and quantitative information built from documents, specific bibliography, and interviews. The article concludes that participatory bodies have occasionally either limited the capture of policies or generated valuable experiences, at least temporarily. However, they have failed to prevent the capture of policies by economic and political elites. Therefore, the influence attained was not enough to produce changes in the communication system. Nevertheless, there have been a number of positive results, albeit unintended and difficult to measure, related to the enrichment of democratic and civic practices.